Multilocus Sequence Typing Scheme for Enterococcus faecium - Homan, Wieger L. (American Society for Microbiology, 2002)
A multilocus sequence typing (MLST) scheme has been developed for Enterococcus faecium. Internal fragments from seven housekeeping genes of 123 epidemiologically unlinked isolates from humans and livestock and 16 human-derived isolates from several outbreaks in the United States, the United Kingdom, Australia, and The Netherlands were analyzed. A total of 62 sequence types were detected in vancomycin-sensitive E. faecium (VSEF) and vancomycin-resistant E. faecium (VREF) isolates. VSEF isolates were genetically more diverse than VREF isolates. Both VSEF and VREF isolates clustered in host-specific lineages that were similar to the host-specific clustering obtained by amplified fragment length polymorphism analysis. Outbreak isolates from hospitalized humans clustered in a subgroup that was defined by the presence of a unique allele from the housekeeping gene purK and the surface protein gene esp. The MLST results suggest that epidemic lineages of E. faecium emerged recently worldwide, while genetic variation in both VREF and VSEF was created by longer-term recombination. The results show that MLST of E. faecium provides an excellent tool for isolate characterization and long-term epidemiologic analysis.